1981
DOI: 10.1007/bf02887317
|View full text |Cite
|
Sign up to set email alerts
|

Lupin protein concentrates by extraction with aqueous alcohols

Abstract: In order to remove the toxic quinolizidine alkaloids and other nonprotein constituents, hexane-defatted flakes of lupin (Lupinus rautabilis) were extracted under various conditions with ethanol, methanol or their aqueous solutions. Lupin protein concentrates containing more than 70% protein and 0.1-0.2% alkaloids were obtained in high yields by consecutive extractions, countercurrent extraction or semicountercurrent extraction of the defatted lupin flakes with either 80% ethanol or 80% methanol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…All species of lupin contain quinolizidine alkaloids to a greater or lesser extent (range: 0–4% of the seed, w/w) (Blaicher et al 1981). Wild lupins have higher levels of alkaloids than domesticated lupin varieties.…”
Section: Off‐flavors In Pulsesmentioning
confidence: 99%
“…All species of lupin contain quinolizidine alkaloids to a greater or lesser extent (range: 0–4% of the seed, w/w) (Blaicher et al 1981). Wild lupins have higher levels of alkaloids than domesticated lupin varieties.…”
Section: Off‐flavors In Pulsesmentioning
confidence: 99%
“…The production of solvents causes more than 80% of the environmental burdens associated with the production of prenilyhydroquinones from S. spinosulus. With this regard, several authors have demonstrated the feasibility of solvent recovery and reuse for the extraction of other metabolites from sponges (Blaicher et al, 1981;Harkrader and Jones, 1998).…”
Section:  Optimization Of Solvent Consumptionmentioning
confidence: 99%
“…The protein content is comparable with that of isolates from many legume sources (Abdel-Aal et a1 1986; Bahnassey et al 1986), unexploited legumes (Blaicher et al 1981;Maza et al 1989), cereals and millets (Bailey and Sumrell 1980;Gopal et a1 1988). The lipid content of the isolate is higher than that reported for most protein concentrates and isolates (Abdel-Aal et a1 1986).…”
mentioning
confidence: 60%